2014
DOI: 10.1007/s11009-014-9412-9
|View full text |Cite
|
Sign up to set email alerts
|

Saddlepoint Approximations to the Probability of Ruin in Finite Time for the Compound Poisson Risk Process Perturbed by Diffusion

Abstract: A large deviations type approximation to the probability of ruin within a finite time for the compound Poisson risk process perturbed by diffusion is derived. This approximation is based on the saddlepoint method and generalizes the approximation for the non-perturbed risk process by BarndorffNielsen and Schmidli (1995). An importance sampling approximation to this probability of ruin is also provided. Numerical illustrations assess the accuracy of the saddlepoint approximation using importance sampling as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Most relative deviations between importance sampling and saddlepoint approximation are below 5% and this coincidence between these two different techniques gives good evidence of high accuracy for these two alternative methods. More comparisons can be found in Gatto and Baumgartner (2014). A numerical comparison for the infinite time horizon probability of ruin can be found in Gatto and Mosimann (2012), where it is again shown that importance sampling and saddlepoint approximation have very small relative deviations.…”
Section: A Numerical Illustrationmentioning
confidence: 95%
See 2 more Smart Citations
“…Most relative deviations between importance sampling and saddlepoint approximation are below 5% and this coincidence between these two different techniques gives good evidence of high accuracy for these two alternative methods. More comparisons can be found in Gatto and Baumgartner (2014). A numerical comparison for the infinite time horizon probability of ruin can be found in Gatto and Mosimann (2012), where it is again shown that importance sampling and saddlepoint approximation have very small relative deviations.…”
Section: A Numerical Illustrationmentioning
confidence: 95%
“…We compute directly the relative deviations of importance sampling w.r.t. the saddlepoint approximation of Gatto and Baumgartner (2014), which is another large deviations technique. Similar approximations are thus expected with both methods.…”
Section: A Numerical Illustrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the particular situation where the loss process S is a compound Poisson process perturbed by a Wiener process, the desired quantityψ(x, t) can be alternatively computed by the saddlepoint approximation to ψ(x, t) suggested by Gatto and Baumgartner (2014), together with the saddlepoint approximation to ζ(x, t) of Gatto (2010). Saddlepoint approximations are substantially faster to compute than importance sampling, although they are conceptually more sophisticated and by far less popular than Monte Carlo methods.…”
Section: Final Remarksmentioning
confidence: 99%
“…By renewal theory, they obtained the Pollaczeck-Khinchin formula of Φ(x). Accurate calculation and approximation for Ψ(x) has always been an inspiration and an important source of technological development for actuarial mathematics (see, e.g., [3][4][5][6][7][8][9]). Although various approximations to the probability of ruin (e.g., importance sampling or saddle-point approximations) are now available, developing alternative approximations of different nature is still an interesting and practical problem.…”
Section: Introductionmentioning
confidence: 99%